Influenza A virus in dairy cattle: infection biology and potential mammary gland-targeted vaccines - Rodrigo Prado Martins; Daniel Marc; Pierre Germon; Sascha Trapp; Ignacio Caballero-Posadas (npj Vaccines)
Abstract Influenza, a major “One Health” threat, has gained heightened attention following recent reports of highly pathogenic avian influenza in dairy cattle and cow-to-human transmission in the USA. This review explores general aspects of influenza A virus (IAV) biology, its interactions with mammalian hosts, and discusses the key considerations for developing vaccines to prevent or curtail IAV infection in the bovine mammary gland and its spread through milk.